The development of an angiogenic protein "signature" in ovarian cancer ascites as a tool for biologic and prognostic profiling - Trachana, S.-P.; Pilalis, E.; Gavalas, N.G.; Tzannis, K.; Papadodima, O.; Liontos, M.; Rodolakis, A.; Vlachos, G.; Thomakos, N.; Haidopoulos, D.; Lykka, M.; Koutsoukos, K.; et al. (PLoS ONE, 2016)
Advanced ovarian cancer (AOC) is one of the leading lethal gynecological cancers in developed countries. Based on the important role of angiogenesis in ovarian cancer oncogenesis and expansion, we hypothesized that the development of an "angiogenic signature" might be helpful in prediction of prognosis and efficacy of anti-angiogenic therapies in this disease. Sixty-nine samples of ascitic fluid- 35 from platinum sensitive and 34 from platinum resistant patients managed with cytoreductive surgery and 1st-line carboplatin-based chemotherapy- were analyzed using the Proteome Profiler™ Human Angiogenesis Array Kit, screening for the presence of 55 soluble angiogenesis-related factors. A protein profile based on the expression of a subset of 25 factors could accurately separate resistant from sensitive patients with a success rate of approximately 90%. The protein profile corresponding to the "sensitive" subset was associated with significantly longer PFS (8 [95% Confidence Interval CI: 8-9] vs. 20 months [95% CI: 15-28]; Hazard ratio HR: 8.3, p<0.001) and OS (20.5 months [95% CI: 13.5-30] vs. 74 months [95% CI: 36-not reached]; HR: 5.6 [95% CI: 2.8-11.2]; p<0.001). This prognostic performance was superior to that of stage, histology and residual disease after cytoreductive surgery and the levels of vascular endothelial growth factor (VEGF) in ascites. In conclusion, we developed an "angiogenic signature" for patients with AOC, which can be used, after appropriate validation, as a prognostic marker and a tool for selection for anti-angiogenic therapies. © 2016 Trachana et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.